2017
DOI: 10.21147/j.issn.1000-9604.2017.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow prognostic score after concurrent chemoradiotherapy is a prognostic factor in advanced head and neck cancer

Abstract: Objective This study aims to evaluate the impact and potential prognostic roles of the pre- and post-treatment Glasgow prognostic score (GPS) and the change thereof in patients with advanced head and neck cancer undergoing concurrent chemoradiotherapy (CCRT).Methods We collected GPS and clinicopathological data of 139 stage III, IVA, and IVB head and neck cancer patients who underwent CCRT between 2008 and 2011. Their GPSs pre- and post-CCRT and the change thereof were analyzed for correlations with recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several common peripheral blood-derived inflammation-based scores, such as the Glasgow Prognostic Score (GPS), NLR, and PLR, have been demonstrated as promising prognostic predictors in various malignancies. 26 28 However, the measurement of serum C-reactive protein was not routinely taken in our hospital before 2005, and therefore, the prognostic value of GPS was not examined in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the mGPS score prior to, during, and after CCRT have been identified as important prognosticators of DFS and OS. Patients exhibiting an improved GPS at the end of treatment have been linked to better OS (p= 0.013) and relapse-free survival (p=0.012) compared with those yielding a worsened final GPS 21…”
Section: Patient-related Factorsmentioning
confidence: 99%